Men's doubles professional tennis on hard courts: Game structure and point ending characteristics - Martinez-Gallego, R.; Crespo, M.; Ramón-Llin, J.; Micó, S.; Guzmán, J. F. (Journal of Human Sport & Exercise, 2020)
Despite the great tradition and importance of the doubles game in professional tennis, no literature has analysed to date the performance of professional players. Therefore, the information on the characteristics of the game, or the tactics related to how the points are won in doubles play is scarce. The objective of this study has been to describe the basic characteristics of the structure of the doubles game, and to establish how the points finish in doubles professional tennis played on hard courts. Thirty-four ATP doubles matches played in 2018 were analysed, which included a total of 40 professional players. As per the game structure, the results showed that, in comparison to the singles matches, the number of points per match, the number of sets per match, the number of points per game, and the number of strokes per point, are lower in the doubles matches. However, the number of games per set is higher in doubles than in singles. Winning shots and winning serves are the most frequent patterns to finish the point in doubles. These data show the great importance of the serve in doubles, as well as the relevance of using offensive tactics.